Whole-organ analysis of TGF-beta-mediated remodelling of the tumour microenvironment by tissue clearing - Kubota, Shimpei I. (University of Dundee, 2021)
Tissue clearing is one of the most powerful strategies for a comprehensive analysis of disease progression. Here, we established an integrated pipeline that combines tissue clearing, 3D imaging, and machine learning and applied to a mouse tumour model of experimental lung metastasis using human lung adenocarcinoma A549 cells. This pipeline provided the spatial information of the tumour microenvironment. We further explored the role of transforming growth factor-beta (TGF-beta) in cancer metastasis. TGF-beta-stimulated cancer cells enhanced metastatic colonization of unstimulated-cancer cells in vivo when both cells were mixed. RNA-sequencing analysis showed that expression of the genes related to coagulation and inflammation were up-regulated in TGF-beta-stimulated cancer cells. Further, whole-organ analysis revealed accumulation of platelets or macrophages with TGF-beta-stimulated cancer cells, suggesting that TGF-beta might promote remodelling of the tumour microenvironment, enhancing the colonization of cancer cells. Hence, our integrated pipeline for 3D profiling will help the understanding of the tumour microenvironment.
Whole lung image of metastatic model mouse.
Keywords: FOS: Biological sciences